2022
DOI: 10.1002/aesr.202200036
|View full text |Cite
|
Sign up to set email alerts
|

Progress in In Situ Research on Dynamic Surface Reconstruction of Electrocatalysts for Oxygen Evolution Reaction

Abstract: Renewable energy and sustainable development have attracted considerable attention due to the rapid growth of energy consumption and environmental pollution. The further development of electrocatalytic water splitting can promote the development and application of next‐generation sustainable energy systems. However, the lack of an in‐depth understanding of the dynamic restructuring process occurring on the catalyst surface in the oxygen evolution reaction (OER) has limited the further development and improveme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 158 publications
0
20
0
Order By: Relevance
“…However, precise identification of real active sites for OER is challenging; it could be achieved using in situ spectroscopic techniques such as Raman spectroscopy, X-Ray photoelectron spectroscopy (XPS), and X-Ray absorption spectroscopy (XAS). [114,115] In this context, in situ Raman spectroscopy is useful to identify the intermediates and structural transformations of the electrocatalysts during electrocatalytic OER by monitoring the changes in low-frequency vibrational modes. [114][115][116][117] For example, Qiu et al [118] observed that the formation of γ-NiOOH was responsible for the improved OER activity of NiFe-LDHs in alkaline media.…”
Section: Parameters Used To Evaluate Electrocatalytic Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…However, precise identification of real active sites for OER is challenging; it could be achieved using in situ spectroscopic techniques such as Raman spectroscopy, X-Ray photoelectron spectroscopy (XPS), and X-Ray absorption spectroscopy (XAS). [114,115] In this context, in situ Raman spectroscopy is useful to identify the intermediates and structural transformations of the electrocatalysts during electrocatalytic OER by monitoring the changes in low-frequency vibrational modes. [114][115][116][117] For example, Qiu et al [118] observed that the formation of γ-NiOOH was responsible for the improved OER activity of NiFe-LDHs in alkaline media.…”
Section: Parameters Used To Evaluate Electrocatalytic Activitymentioning
confidence: 99%
“…[114,115] In this context, in situ Raman spectroscopy is useful to identify the intermediates and structural transformations of the electrocatalysts during electrocatalytic OER by monitoring the changes in low-frequency vibrational modes. [114][115][116][117] For example, Qiu et al [118] observed that the formation of γ-NiOOH was responsible for the improved OER activity of NiFe-LDHs in alkaline media. The presence of Fe 3þ influenced the oxidation of Ni 2þ into γ-NiOOH, which was identified as the OER active phase by in situ Raman spectroscopy.…”
Section: Parameters Used To Evaluate Electrocatalytic Activitymentioning
confidence: 99%
“…Although several recent reviews have well addressed diverse examples of phase evolution during electrocatalysis, [58] our review is providing well-organized design guidelines by distinguishing the type of metal oxide (e.g., TM and precious metal), electrolyte conditions (e.g., alkaline and acidic electrolytes), and strategies (e.g., facilitation and protection). [59] Before looking at experimental examples, theoretical predictions of the leaching and surface reconstruction processes can be of great help during the material design stage. Such leaching processes can be explained by a Pourbaix diagram analysis, which can be calculated from the Gibbs free energy of the decomposition of each phase under a certain pH and applied potential.…”
Section: Cation Movements From Surface To the Surroundings: Inside-to...mentioning
confidence: 99%
“…1,2 Water electrolysis involving anodic oxygen evolution reactions (OERs) and cathodic hydrogen evolution reactions (HERs) is regarded as a promising technology for large-scale hydrogen production. 3,4 However, the efficiency of overall water splitting is seriously hampered by the anodic half-reaction, which involves a four-electron process. 5,6 Currently, the state-of-the-art OER electrocatalysts are Ru/Ir and their oxides, mainly due to their suitable electronic structure and good durability.…”
Section: Introductionmentioning
confidence: 99%